Odpowiedzi

Najlepsza Odpowiedź!
2009-12-17T17:43:27+01:00
3x + 4y = 1 i 2/3
6x + 3y = 1 i 1/4

3x + 4y = 5/3 /*3
6x + 3y = 5/4 /*4

9x + 12y = 5
24x + 12y = 5

12y = 5 - 9x
24x + 5 -9x = 5

12y = 5 -9x
15x = 5 -5

12y = 5 -9x
15x = 0

12y = 5 -9x
x = 0

12y = 5 -9*0
x = 0

12y = 5 /:12
x = 0

y = 5/12
x = 0

x = 0
y = 5/12

2009-12-17T17:48:47+01:00
3x + 4y = 1 i 2/3
6x + 3y = 1 i 1/4


3x+4y=1 i 2/3
6x=1 i 1/4 -3y


5/8-1i 1/2y +4y=1 i2/3
3x=5/8 -1i 1/2 y


3x=5/8 -1i 1/2 y
2 i 1/2 y = 1/24

3x=5/8 -1i 1/2 y

y=1/60

3x=5/8-1 i 1/2 * 1/60
3x= 24/40
3x=12/20
3x=3/5
x=3/15